(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Demonetization means Withdrawal of a particular form of currency from circulation. The reasons of demonetization are tackle black money, eliminate fake currency, control on corruption etc. In demonetization overall economic activities will be dampened in the short term. But the immeasurable benefits of having more transparency and reduced volume of black money activities can be pointed as long term benefits. The paper discussed impact of demonetization on key factors like General people, Stock market, Transportation, Agriculture, Banking, Business, Income tax, Insurgent groups, Railways , Jewelers etc.